PENGUKURAN KINERJA MANAJEMEN RANTAI PASOK PADA CV. BERAS PUSPA JOGED BALI - Wulandari, Kadek Popy; Nurcaya, I Nyoman (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.02.TAHUN.2023, 2023)
Supply chain management is the integration of the production process, starting from the procurement of raw materials and ending with the delivery of products to consumers. The implementation of this system affects the company's overall performance, so it is necessary to measure performance to determine the productivity that has been achieved. This research was conducted on CV. Beras Puspa Joged Bali, which sometimes suffers from a shortage of production raw materials, so it is necessary to bring them in from outside the Bali area with greater risk during expeditions. This study aims to determine the performance of supply chain management CV. Beras Puspa Joged Bali, which includes supply chain reliability, responsiveness, cost, and asset management performance. Interview and observation methods are used to get the data, as well as data analysis methods that use the Supply Chain Operations Reference (SCOR) model. The calculation results show the Perfect Order Fulfillment (POF) metric value of 99.88%, the Order Fulfillment Cycle Time (OFCT) metric for 3 days, the Cost of Goods Sold (COGS) metric of 86%, and the Cash to Cash Cycle Time (CTCCT) metric for 20 days